Disaster Confrontation Mechanisms within Local Efforts at the Governorate Level - Youzbakey, Kotayba T. Al- (Journal of Risk and Crisis Management, 2020)
The current study aims to shed light on the importance of preparing plans to confront disasters of all-natural and abnormal types in order to avoid the aggravation of the disaster crisis. And the adoption of the available local capabilities in preparing these plans in a manner consistent with achieving the minimum possible losses in individuals and their private and public property. The study is based on identifying the wrong features of disaster management for the purpose of avoiding them when preparing successful and effective plans during their implementation, determining the local data on which the disaster management plan is based, and proposing a comprehensive management plan model that can be modified according to the type of disaster required to be confronted.This study deals with ways to prepare a plan to deal with any disaster according to local data at the governorate level, and propose the method of coordination among the implementing entities, especially the formations of the army and the internal security forces by using the expertise and capabilities that exist within the departments in the governorate, to perform the best genealogy by executing orders, avoid unexpected losses and to achieve the objectives of the plan in an integrated manner. This research was discussed in the mechanism, foundations and objectives of disaster and crisis management plans, which must be provided in the preparation of any plan for the purpose of ensuring its success and achieving positive returns, either preventing a disaster or mitigating as much as possible its negative effects on human beings, whether direct or indirect and his private and public properties. Make the disaster management program one of the strategic tasks of governments within sustainable development plans by joining local institutions in developing their capacity to implement disaster response programs. The Government is also working on the development of subsidiary bodies in its institutions to diagnose risks and to create technical and specialized cadres implemented and supported according to the type of such risks within their department of work. In addition to developing a culture of disaster prevention in the society in general and highlighting the role of the citizen in activating the process of confrontation the disasters.The study recommends making the disaster management program one of the basic tasks and programs in the sustainable development strategy and plans, with the concerted state institutions within the province to enhance their capabilities to deal with disasters by creating bodies or subsidiary institutions to diagnose and monitor risks and train their cadres technically, Taking into consideration the need to develop a culture of disaster prevention among citizens.
Keywords: Natural hazards; disaster management; crises; physical hazards; disaster confrontation